Analysis of doxorubicin and fullerenol in rat serum by micellar electrokinetic capillary chromatography - Injac Rade; Sertić Miranda; Glavač Nina Kočevar (Acta Pharmaceutica)
A new micellar electrokinetic capillary chromatographic (MEKC) method has been developed and optimized for simultaneous quantitation of doxorubicin (Dox) and fullerenol (Frl) in rat serum. The separation was carried out in a capillary (48.5–40 cm to the detector – 50 µm id fused-silica capillary with bubble cell, 150 µm) at an applied voltage of 25 kV and temperature of 25 °C. For the background electrolyte 10 mmol L–1 borate buffer pH 9.3 plus 15 mmol L–1 phosphate buffer pH 7.0 (with the final pH of the mixture adjusted to 7.0 with HCl), with added 10 % (V/V) methanol, and 15 mmol L–1 sodium dodecyl sulfate as a surfactant, were used. The hydrodynamic injection was carried out at 5.0 kPa during the period of 100 s. Linear calibration curves were established over the concentration range 0.5–500.0 mg L–1 for Dox and 10.0–500.0 mg L–1 for Frl (at 234 nm). The proposed MEKC procedure was fully validated and applied for the deter mination of Dox and Frl in Wistar rats after intra pe ritoneal administration of both molecules.